The Neo-Assyrian empire in the southwest: imperial domination and its consequences - Faust, Avi (Oxford scholarship online, 2021)
The Neo-Assyrian empire - the first large empire of the ancient world - has attracted a great deal of public attention ever since the spectacular discoveries of its impressive remains in the 19th century. The southwestern part of this empire, located in the lands of the Bible, is archaeologically speaking the best known region in the world, and its history is described in a plethora of texts, including the Hebrew Bible. Using a bottom-up approach, Avraham Faust utilises this unparalleled information to reconstruct the outcomes of the Assyrian conquest of the region and how it impacted the diverse political units and ecological zones that comprised it. In doing so, he draws close attention to the transformations the imperial take-over brought in its wake.